Uji Daya Hambat Ekstrak Sawo Manila Terhadap Pertumbuhan Salmonella thypi - Anita Anita; Nurul Ni'ma Azis; Eka Safitri (Lontara Journal of Health Science and Technology, 2020)
Sawo manila (Manilkara zapota) is a plant that is traditionally used to treat several types of diseases, one of which is typhoid fever. Sawo manila (Manilkara zapota) is safe for consumption because it does not have harmful effects on the human body. The purpose of this study was to determine the ability of extracts to inhibit the growth of Salmonella thypi. Sawo manila (Manilkara zapota) was extracted with 70% ethanol using maceration method. This type of research is experimental laboratory. Antibacterial activity test was carried out using the diffusion method to be layered n the Muller Hilton Agar (MHA) medium and an incubation period of 24 hours at 370C. The test results showed that sawo manila at a concentration of 50% showed the presence of inhibition zones with a diameter of I: 4 mm, II: 5 mm, III: 6 mm and at a concentration of 100% also showed the presence of inhibition zones with a diameter of I: 11 mm, II: 13 mm, III: 12 mm. From the results of the study showed Sawo manila (Manilkara zapota) can effectively inhibit Salmonella thypi so that it can be used as an alternative treatment.